FAKTOR EKSPLOITASI PADA HUTAN PRODUKSI TERBATAS DI IUPHHK-HA PT KEMAKMURAN BERKAH TIMBER - Soenarno; Dulsalam; Wesman Endom (BRIN Publishing, 2013)
In timber harvesting, exploitation factor is implemented as the one parameters to determine the allocated annual production at the natural production forest. Currently, the value of exploitation factor as stipulated by the Ministry of Forestry that applies to all conditions of natural production forest exhibits large varying-topographies and in operation tends to be beavier than tost at either the fixed production forest or convertible production forest. The situation brought about a significant difference in the exploitation factors (EF) during the timber harvesting. In average the value of EF at the Licensed Natural Forest Concessionary PT. Kemakmuran Berkah Timber reached 0.92, while the EF at flat topography (0-8) was 0.93; at moderately sloping (9-15'), rather steep (16-25), and steep topographies (26-40) were all similar, i.e. 0.92.